2019
DOI: 10.1007/s00441-019-03160-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth, stemness, and angiogenic properties of dental pulp stem cells cultured in cGMP xeno-/serum-free medium

Abstract: This study was aimed to investigate the effects of cGMP xeno-/serum-free medium (XSF, Irvine Scientific) on the properties of human dental pulp stem cells (DPSCs). DPSCs, from passage 2, were cultured in XSF or fetal bovine serum (FBS)-supplemented medium, and sub-cultured up to passage 8. Cumulative population doublings (PDs) and the number of colony-forming-units (CFUs) were determined. qRT-PCR, ELISA, and in vitro assays were used to assess angiogenic capacity. Flow cytometry was used to measure CD73, CD90,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…When post-bioreactor MSCs were seeded back into their normal culture medium in a 2D adherent state (flask-based), cells were shown to completely restore their CD105 levels up to a degree matching the expression level of the pre-bioreactor processed cells. Akin to our results for the plasticity of the CD105 expression level, Qu et al observed similar results where MSCs re-expressed CD105 after the cells grown under serum-free conditions were seeded back into serumcontaining medium [44]. Noteworthy, in contrast to the cells, analysis of the EV immunophenotyping surface marker profile did show the presence of CD105 expression level on EVs produced throughout the 25-day production scheme, suggesting that the MSCs still produced CD105 when inoculated into the bioreactor, but regulated its expression towards the EVs instead of the cellular membrane.…”
Section: Discussionsupporting
confidence: 87%
“…When post-bioreactor MSCs were seeded back into their normal culture medium in a 2D adherent state (flask-based), cells were shown to completely restore their CD105 levels up to a degree matching the expression level of the pre-bioreactor processed cells. Akin to our results for the plasticity of the CD105 expression level, Qu et al observed similar results where MSCs re-expressed CD105 after the cells grown under serum-free conditions were seeded back into serumcontaining medium [44]. Noteworthy, in contrast to the cells, analysis of the EV immunophenotyping surface marker profile did show the presence of CD105 expression level on EVs produced throughout the 25-day production scheme, suggesting that the MSCs still produced CD105 when inoculated into the bioreactor, but regulated its expression towards the EVs instead of the cellular membrane.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, late passage cultures demonstrated small but apparent differences in this characteristic expression pattern including a reduced CD90 population and increased negative marker population (Supplementary Figure S2A). Though changes to MSC surface marker profiles have been noted in late passage MSCs, the loss of CD90 which is considered a robust marker of MSC identity has not been previously recorded to our knowledge [20][21][22][23][24][25][26]. The presence of T2DM in the host did not affect this characteristic expression pattern in early passages (Figure 2A) or the altered expression at late passages (Supplementary Figure S2B,C).…”
Section: Cell Surface Characterisation and Cumulative Population Doubmentioning
confidence: 73%
“…According to in vitro research, both fresh and cryopreserved dental MSCs isolated from humans and animals successfully meet mesenchymal stem cell criteria. Maxillofacialderived MSCs express MSC and neural crest-related genes and markers including STRO-1, CD13, CD29, CD44, CD59, CD73, CD90, CD105, CD106, and CD146 and were negative for hematopoietic lineage markers including CD14, CD31, CD34, and CD45 [3,7,8,[30][31][32][33][34][35][36][37][38] (Table 1).…”
Section: Characteristics Of Maxillofacial-derived Mesenchymal Stem Sellsmentioning
confidence: 99%